Gene Expression in Class 2 Integrons Is SOS-Independent and Involves Two Pc Promoters - Jové, Thomas; Da Re, Sandra; Tabesse, Aurore; Gassama-Sow, Amy; Ploy, Marie-Cécile (Frontiers in Microbiology, 2017)
Integrons are powerful bacterial genetic elements that permit the expression and dissemination of antibiotic-resistance gene cassettes. They contain a promoter Pc that allows the expression of gene cassettes captured through site-specific recombination catalyzed by IntI, the integron-encoded integrase. Class 1 and 2 integrons are found in both clinical and environmental settings. The regulation of intI and of Pc promoters has been extensively studied in class 1 integrons and the regulatory role of the SOS response on intI expression has been shown. Here we investigated class 2 integrons. We characterized the PintI2 promoter and showed that intI2 expression is not regulated via the SOS response. We also showed that, unlike class 1 integrons, class 2 integrons possess not one but two active Pc promoters that are located within the attI2 region that seem to contribute equally to gene cassette expression. Class 2 integrons mostly encode an inactive truncated integrase, but the rare class 2 integrons that encode an active integrase are associated with less efficient Pc2 promoter variants. We propose an evolutionary model for class 2 integrons in which the absence of repression of the integrase gene expression led to mutations resulting in either inactive integrase or Pc variants of weaker activity, thereby reducing the potential fitness cost of these integrons.